Morphological and Histological Evaluation in Suspected Cases of Sudden Cardiac Death: A Cross Sectional Study - Pandit , J N; Arava , S K; Yadav , A; Prasad , K; Gupta , S K (Journal of Indian Academy of Forensic Medicine, 2023)
During the autopsy, acute plaque changes such as occluding thrombus, atheromatous disruption, or both are seen in more than half of  sudden coronary death cases. At the department of Forensic Medicine and Toxicology, we are getting the cases of sudden cardiac death  (SCD) frequently for medico-legal autopsy. The majority of these are found to be due to coronary insufficiency which had been  unexpected and unexplained on history taking before the autopsy. Even during the autopsy, some cases do not show any evident gross  findings and the diagnosis of SCD can only be made by microscopic examination of the heart and after excluding other possible causes of  death. Thus, forensic pathologists have a great opportunity to study SCD and its relationship with different organic and functional causes.  The authors have conducted this study intending to evaluate the morphological findings and histopathological changes in suspected cases  of sudden cardiac deaths. In this cross-sectional study, the gross pathologies were seen as petechial hemorrhage, soldier's patches,  coronary occlusion, bridging of coronary arteries, cardiac tamponade, aortic dissection, valvular pathology, and recent or remote changes  of ischemia in the myocardium, etc. Most commonly, the coronary artery occlusions were seen in LAD (59%), especially in its proximal  portion (47%). Grade I ischemic changes were seen in maximum cases (in 23% cases), followed by Grade III (in 20% cases), then Grade II  (in 16% cases) and least as Grade IVischemic changes seen in 2% of cases.
Keywords: Sudden cardiac death; Histopathological examination; Thrombo-atheromatous plaque; MT and VVG staining; Myocardial bridging; Myocardial ischemia